Science education development : a philosophical analysis of conflict between scientific and Islamic perspectives / Yaacob Yusoff Awang - Yusoff Awang, Yaacob (Universiti Teknologi MARA, Sarawak, 2003)
The whole corpus of education in the Muslim world has been heavily influenced and shaped by the Western concept of education. So much so that it has led to anxiety among present Muslim scholars. it is openly acknowledged that the aim of education in the West is to produce a good individual and good citizen, both of which Islam can also accept. However, having been secularised, science fails to achieve, particularly in the absence of a set of moral values, either of those aims.